КОЭФФИЦИЕНТИ УЗИЛИШГА ЭГА БЎЛГАН ОДДИЙ ДИФФЕРЕНЦИАЛ ТЕНГЛАМА УЧУН УМУМЛАШГАН СПЕКТРАЛ МАСАЛА (Scientific journal of the Fergana State University, 2018)
In the article a generalised spectral problem with the second kind integral condition for the linear ordinary differential equation with discontinuous coefficient  is  investigated.  Eigenvalues and eigenfunctions of the considered problem are found out.